PENINGKATAN INOVASI KULINER LOKAL DESA WISATA KOTA SEMARANG - Tuwuh Adhistyo Wijoyo; Krisnawati S.N; Aletta Dewi M (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
Community service by conducting counseling carried out by the lecturer team from STIEPARI Semarang in terms of increasing local culinary innovations for Semarang City Tourism Village has succeeded in having an impact on the community in the Semarang City Tourism Village environment. Tourism village is a big potential for regional development, especially Semarang City. The tourist village in the city of Semarang has a different potential which becomes an advantage and strength. The diversity of themes and concepts of a tourist village will become a diversity that can show its existence, especially for the city of Semarang which incidentally is an urban area. The diversity of tourism villages can be drawn from one thing in common, that each tourist village has similarities in terms of culinary delights. The culinary in the tourist village has its own characteristics which are influenced by the geographical and cultural location in the tourist village as well as local products which are the advantages of each tourist village. It is felt that the culinary development in the tourist village has not changed because it has not been touched much in terms of innovations that can be done.